Prx1 Expressing Cells Are Required for Periodontal Regeneration of the Mouse Incisor - Bassir, Seyed Hossein; Garakani, Sasan; Wilk, Katarzyna; Aldawood, Zahra A.; Hou, Jue; Yeh, Shu-Chi A.; Sfeir, Charles; Lin, Charles P.; Intini, Giuseppe (Frontiers in Physiology, 2019)
Previous studies have shown that post-natal skeletal stem cells expressing Paired-related homeobox 1 (PRX1) are present in the periosteum of long bones where they contribute to post-natal bone development and regeneration. Our group also identified post-natal PRX1 expressing cells (pnPRX1+ cells) in mouse calvarial synarthroses (sutures) and showed that these cells are required for calvarial bone regeneration. Since calvarial synarthroses are similar to dentoalveolar gomphosis (periodontium) and since there is no information available on the presence or function of pnPRX1+ cells in the periodontium, the present study aimed at identifying and characterizing pnPRX1+ cells within the mouse periodontium and assess their contribution to periodontal development and regeneration. Here we demonstrated that pnPRX1+ cells are present within the periodontal ligament (PDL) of the mouse molars and of the continuously regenerating mouse incisor. By means of diphtheria toxin (DTA)-mediated conditional ablation of pnPRX1+ cells, we show that pnPRX1+ cells contribute to post-natal periodontal development as ablation of pnPRX1+ cells in 3-days old mice resulted in a significant enlargement of the PDL space after 18 days. The contribution of pnPRX1+ cells to periodontal regeneration was assessed by developing a novel non-critical size periodontal defect model. Outcomes showed that DTA-mediated post-natal ablation of pnPRX1+ cells results in lack of regeneration in periodontal non-critical size defects in the regeneration competent mouse incisors. Importantly, gene expression analysis of these cells shows a profile typical of quiescent cells, while gene expression analysis of human samples of periodontal stem cells (PDLSC) confirmed that Prx1 is highly expressed in human periodontium. In conclusion, pnPRX1+ cells are present within the continuously regenerating PDL of mouse incisor, and at such location they contribute to post-natal periodontal development and regeneration. Since this study further reports the presence of PRX1 expressing cells within human periodontal ligament, we suggest that studying the mouse periodontal pnPRX1+ cells may provide significant information for the development of novel and more effective periodontal regenerative therapies in humans.